Isililo sikaNandi: imagining dithyrambic dirge to performatively score the precarity of blackwomnhood - Nkonyeni, Zamah Martiniah (Centre for Film and Media Studies, 2023)
This study is an exploration of an embodied awareness and the plethora of ways in which what I am ‘falls short' - in relation to being “fully human” (Lugónes, 2010:743). It serves as the creative stimulus to actively explore and resist the ontological arrest of my blackwomnhood. This work aspires towards a kind of social and embodied resistance by means of “deserting exceptionality” (Gqola, 2004:61). As a form of survival, as well as of repairing the ruptured fragments of my being, I want to redefine, for myself, through performance, what it means to be a young, South African, working-class, queer blackwomn. This study therefore necessitates a distinction between ‘who' I am and ‘what' I am through exploring what Adriana Cavarero refers to as the ‘narratable self' (2005: x) in conjunction with Barbara Boswell's ‘creative re-visioning' (2010:1) and what Audre Lorde defines as ‘autobiomythography' (Lorde, 1996). In order to do this, the study employs a Practice as Research approach to explore alternative ways of staging heterogeneous experiences of blackwomnhood using the plurality of voice as a performance mode/tool. This study further reflects on a series of performance projects (as part of the present MA) to interrogate and reflect critically on the scale and complexity of the work/s. Following Cavarero (2005: x), Boswell (2010:1) and Lorde (1996), I explore the oral historical narratives and timelines of Zulu matriarch, Queen Nandi, to imagine a dithyrambic dirge drawn from blackwomn's experiences of ruptures, reckonings and refusals.